2011
DOI: 10.1063/1.3609964
|View full text |Cite
|
Sign up to set email alerts
|

Defect-induced magnetism in undoped wide band gap oxides: Zinc vacancies in ZnO as an example

Abstract: To shed light on the mechanism responsible for the weak ferromagnetism in undoped wide band gap oxides, we carry out a comparative study on ZnO thin films prepared using both sol-gel and molecular beam epitaxy (MBE) methods. Compared with the MBE samples, the sol-gel derived samples show much stronger room temperature ferromagnetism with a magnetic signal persisting up to ∼740 K, and this ferromagnetic order coexists with a high density of defects in the form of zinc vacancies. The donor-acceptor pairs associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(73 citation statements)
references
References 81 publications
(84 reference statements)
7
66
0
Order By: Relevance
“…Ferromagnetism has been observed previously in undoped thin films and nanoparticles of TiO 2 , HfO 2 , In 2 O 3 , CaO, and CeO 2 . 43,44 This phenomenon is generally recognized as the d 0 magnetism, [45][46][47][48][49] and its origin is usually linked to structural defects. 43,44,50 But the d 0 magnetism is usually very weak, comparable to the magnetic signal observed in our as-grown ZnO NW sample (UZO).…”
mentioning
confidence: 99%
“…Ferromagnetism has been observed previously in undoped thin films and nanoparticles of TiO 2 , HfO 2 , In 2 O 3 , CaO, and CeO 2 . 43,44 This phenomenon is generally recognized as the d 0 magnetism, [45][46][47][48][49] and its origin is usually linked to structural defects. 43,44,50 But the d 0 magnetism is usually very weak, comparable to the magnetic signal observed in our as-grown ZnO NW sample (UZO).…”
mentioning
confidence: 99%
“…Despite the above theoretical predictions, no satisfactory experimental observations are available in the literature to justify the source of p-type conductivity. Coincidentally, as a matter of concern, defects in ZnO could also induce ferromagnetism [20]. However, in those theoretical studies, authors did not investigate whether magnetism has been induced on arsenic doping.…”
Section: Introductionmentioning
confidence: 98%
“…Transition metal ion-doped ZnS nanoparticles are studied extensively to explore their structural, optical, luminescence and magnetic properties. The literature shows that many authors have reported the transition metal ion (Mn, Co, Ni, and Fe)-doped ZnS nanoparticles with different techniques [5][6][7][8][9][10][11][12]. ZnS exists in cubic and hexagonal structure with wide bandgap of 3.54 and 3.91 eV, respectively, and therefore becomes the potential candidate among II-VI group to tailor its properties [13][14][15].…”
Section: Introductionmentioning
confidence: 99%